The use of ritual as physical and spiritual medium and its documentation in Buhlebezwe Siwani's contemporary visual arts performance - Lila, Philiswa (Rhodes University, Faculty of Humanities, Department of Fine Art, 2020)
This thesis is motivated by my experience of Inzilo: Ngoba ngihlala kwabafileyo, a live performance by South African visual artist Buhlebezwe Siwani. The performance took place at Michaelis Galleries, University of Cape Town (UCT), as part of a group exhibition Between Subject and Object: human remains at the interface of art and science (2014), which accompanied the Medical Humanities in Africa Conference (from 28 "“ 29 August 2014). As an entry into my discussion, I describe how Siwani's performance makes use of death and burial ritual in what seems to be an intention to make art that is (re)presenting an activity of reality to invade and control the sphere of feelings, emotions and a sense of ceremony that is dependent on both ritual and rites of the performance. I grapple with the fact that I experienced a ritual performance in a gallery space. Furthermore, I question how walking out of the performance I thought of the lines between art and/or life. The role of ritual in my thesis explores the symbolic meanings, powers and intentions of ritual rites in Africa. This reflection maps out historical locations that are relevant to the major debates, definitions, themes and the experiences of ritual as part of academic research. From Siwani's practice as an artist and isangoma to other expressions in the fields of history, sociology, religion, feminism, to mention a few, my thesis is an enquiry that engages ritual and performance art theory and scholarship. Through a qualitative analysis, my methodology rejects a chronological, thematic and discipline centered research. Rather, I use a multidisciplinary approach based on critical visual analysis as knowledge creation in the visual arts, for example archives, documentation, performance, text, video, installation, painting, sculpture, etc. The findings suggests that the role of ritual in performance art is not a singular exploration, nor is it based on separating ritual and performance art. The results further reveal that ritual in performance art is not a reenactment of patterns and human behaviours, nor is the notion of reenactment used to denote the myriad meanings and functions of re-performing historical ritual events into performance art. Throughout, my thesis provides a focus that demonstrates the significance of how ritual in performance art has a profound subjective (personal or individual) and collective holistic way of serving human and spiritual needs, and that of creating an environment that is open to the content and context of art as it relates with traditional African religious practices, beliefs and knowledges. Focus is given to three major themes that make up the three chapters of my research: firstly, I reflect on death as personified by Siwani's performance Inzilo: Ngoba ii ngihlala kwabafileyo and her role as isangoma. Here death is used to draw specific attention to the body in process of embodied presence and absence of physical and spiritual worlds. Secondly, drawing on Siwani's concept of secrecy and boundaries of concealing and revealing rituals meanings and powers as isangoma, I question the role of secrets, which highlights the significance of bodies (human and natural sites of ritual) in ritual performance. Finally, the idea of a trace is explored. The intersecting use of a trace as the thinking-making-doing of ritual in performance articulates a connected thread that sets in motion the trace of ritual (installation, image and marked space pf ritual) as an afterlife that offers a continued space of processual ceremony for multiple effective encounters and movements..
Keywords: Arts and religion; Ritual -- South Africa; Performance art -- Religious aspects -- South Africa; Women performance artists -- South Africa; Siwani, Buhlebezwe, 1987-